Effects of supplementing feedlot steers and heifers with Zilpaterol hydrochloride on Warner-Bratzler Shear Force of steer longissimus lumborum and heifer longissimus lumborum, triceps brachii and gluteus medius muscles aged for 7, 14 and 21 days - Claus, Heidi L. (Kansas State University, 2009)
The longissimus lumborum (LL) muscle from 117 steers and the LL, gluteus medius (GM), and triceps brachii (TB) from 132 heifers were obtained to evaluate the effects of feeding zilpaterol hydrochloride (Zilmax®; ZH) (7.56g/907kg on a 100% DM basis) on tenderness. Both genders were blocked by initial weight into 6 blocks of 4 pens. Pens were assigned to treatments of either 0, 20, 30 or 40 d on ZH, with a 3 d withdrawal. One steak was removed from each muscle for proximate analysis and three 2.54 cm thick steaks were vacuum aged for either 7, 14 or 21 d. Steaks were cooked to 70 ˚C and six 1.27 cm diameter cores were removed for Warner-Bratzler shear force (WBSF) determinations. All muscles from steers and heifers fed 30 and 40 d with ZH, had higher (P < 0.05) WBSF compared with controls. The WBSF of steer LL and heifer TB from the 20 d treatment was higher (P < 0.05) than controls. There were no treatment by aging interactions (P > 0.05) for WBSF of steaks from steer LL, heifer LL or heifer TB, but there was a treatment by aging interaction (P < 0.05) for WBSF of steaks from heifer GM. There were no differences (P > 0.05) in percent intramuscular fat for any muscle due to treatment. When using percent intramuscular fat as a covariate, differences in WBSF of steer LL and heifer TB were not altered, but there were slight differences in heifer LL and GM WBSF due to treatment when compared with not using percent fat as a covariate. Percentages of steaks with WBSF ≥ 5 kg increased as days on ZH increased and decreased as days of aging increased. Warner-Bratzler shear force values among the three aging times for steer LL control, 20 and 40 d treatments; all heifer LL treatments, and heifer TB 20 d were all positively correlated (P < 0.01) with each other. Feeding ZH for 20 d generally increased WBSF values, but means were still acceptable. Feeding ZH for 40 d was very detrimental to tenderness.
Keywords: Zilpaterol hydrochloride; Longissimus lumborum; Gluteus medius; Warner-Bratzler shear force; Triceps brachii; Beef cattle; Agriculture, Animal Culture and Nutrition (0475)